THE EFFECTIVENESS OF MEMORY TRICKS GAME IN TEACHING GRAMMAR - Cicilia Ningsi; Taufik Suadiyatno; K. Dedy Sandiarsa S. (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2017)
This research was aimed to find out the effectiveness of Memory Tricks game in teaching grammar. The research was experimental research and the design that was used was pre-test and post-test design. The population of the study was the first grade students of SMKN 1 Kuripan especially in TKJ (TeknikKomputer and Jaringan) course which consisted of three classes. Two classes were chosen as the samples, those were TKJ 1 Class as experimental group consisted of thirty five students and TKJ 3 Class as control group consisted thirty five students. They were chosen by usingSimple Random Sampling technique. Experimental group was treated by Memory Tricks game and control group was treated by Verb Search game. The instrument that was used objective test in forms of completion items test. Then, the scores were analyzed by using statistical analysis. It showed the mean score of experimental group was 76 while the mean score control group was 69.2 and the value of t (t test) = 2,7922 was higher than the value of  (t table) = 1.9955 at the significance level of 0.05% and the number of degree freedom (68). Therefore, according to the result of the analysis, it can be concluded that there is a significant difference between student’s grammar scores taught by Memory Tricks game and taught by Verb Search game. In other words, Memory Tricks game is effective in teaching grammar.